Answer:
Step-by-step explanation:
i agree
Answer:
42+106=x
148=x
Step-by-step explanation:
Remember, -(-x)=x because the negatives cancel out
so
when p=-6 and q=7
p+(-q)-3
-6+(-7)-3
-6-7-3
-13-3
-16
To find the mean, add the numbers, and divide by the amount of numbers there is.
(82 + 105 + 247 + 119 + 94 + 202)/6
Simplify. Remember to follow PEMDAS. First, add
(849)/6
Next, divide by 6
849/6 = 141.5
141.5 should be your answer
hope this helps
Answer:
4-4=0
16-6-10=0
17-3-4-10=0
1-2+1=0
Step-by-step explanation: